Appropriate control methods for mobile virtual exhibitions - Li, Yue; Tennent, Paul; Cobb, Sue (Springer, 2018)
It is becoming popular to render art exhibitions in Virtual Reality (VR). Many of these are used to deliver at-home experiences on peoples’ own mobile devices, however, control options on mobile VR systems are necessarily less flexible than those of situated VR fixtures. In this paper, we present a study that explores aspects of control in such VR exhibitions - specifically comparing ‘on rails’ movement with ‘free’ movement.We also expand the concept of museum audio guides to better suit the VR medium, exploring the possibility of embodied characterguides. We compare these controllable guides with a more traditional audio-guide. The study uses interviews to explore users’ experience qualitatively, as well as questionnaires addressing both user experience and simulator sickness. The results suggest that users generally prefer to have control over both their movement and the guide, however, if relinquishing movement control, they prefer the uncontrolled guide. The paper presents three key findings: (1) users prefer to be able to directly control their movement; (2) this does not make a notable difference to simulator sickness; (3) embodied guides are potentially a good way to deliver additional information in VR exhibition settings.